Implementation of Sequential Search Method on Android-based Jakabaring Dictionary - Suhar Tini (Jurusan Teknologi Informasi Universitas Semarang, 2018)
Language becomes a medium of socializing between individuals with one another, one group with another group, and society one with other communities. However, society with one another does not necessarily have the same language. Therefore it takes a tool or media to communicate between tribes or communities, such as translators or dictionaries. Dictionary applications based on android more desirable users than web-based dictionaries. That's because the android-based dictionary is easier to operate and faster operation, without having to open the web and look up the address of the dictionary. In the process of searching the meaning of vocabulary there are several data search methods. One of them Sequential Search Method or called a search streak that can be used to perform data search, both on the array that has been sequenced or not sorted. Keywords: Dictionary, Jakabaring, Android, Sequential Search, and SQLite.